Research on Government-Enterprise Regulation of Online Car-Hailing Based on Differential Game - Yang, Mingge; Liu, Yajie; Sun, Lulu; Wang, Danning; Liang, Xiaozhen (Frontiers in Psychology, 2022)
In the Internet Era, with the widespread application of digital technology, the way people travel has changed. Compared with traditional taxis, more and more people prefer to choose online car-hailing. The rapid development of the online car-hailing industry has solved the problem of taxi-hailing to a certain extent, but it has also brought some new problems. In order to change the dilemma of the online car-hailing industry, it is necessary to strengthen the regulation of the online car-hailing industry. In this paper, we consider the regulatory system composed of a local government and an enterprise, and use differential game to study the regulation of online car-hailing. In Nash non-cooperative game, Stackelberg master-slave game and cooperative game, we respectively investigate the following indicators, such as the optimal regulatory effort of the government, the optimal regulatory effort of the enterprise, the optimal benefit function of the government, the optimal benefit function of the enterprise, the optimal benefit function of the system, the optimal trajectory of the service quality level for the enterprise and the optimal trajectory of the goodwill for the enterprise. Moreover, we analyze the corresponding conclusions through examples. We obtain some important results. i) In Stackelberg master-slave game, the optimal ratio of the local government subsidy to the enterprise’s regulatory cost is only related to the benefit distribution coefficient and has nothing to do with other factors. ii) Compared with Nash non-cooperative game, the optimal regulatory effort of the local government remains unchanged in Stackelberg master-slave game, but the optimal benefit of the local government increases. Moreover, when the benefit distribution coefficient is greater than 1/3, both optimal regulatory effort and optimal benefit of the enterprise increase. iii) Compared with Stackelberg master-slave game, in cooperative game, the optimal regulatory effort of both government and enterprise increase, and the system optimal benefit also increases. iv) From Nash non-cooperative game to Stackelberg master-slave game and then to cooperative game, when the benefit distribution coefficient is greater than 1/3, the service quality level and goodwill of the enterprise all increase.